Beyond Status Quo: Why is Transdisciplinary Communication Instrumental in Innovation? - James Lipuma; Cristo Leon (Journal of Systemics, Cybernetics and Informatics)

(untitled)
In an era of rapid technological advancements and complex societal challenges, the imperative for disruptive innovation has never been more acute. The International Multi-Conference on Complexity, Informatics, and Cybernetics (IMCIC) 2024 served as a confluence for thought leaders across the domains of Complexity, Informatics, and Cybernetics to explore the relationship between Transdisciplinary Communication (TDC) and disruptive innovation. This presentation highlighted that TDC's unique toolkit complements and is crucial in bridging diverse fields of study. TDC is essential for fostering innovation capable of transcending traditional boundaries and instigating profound systemic change. Drawing upon various collaborative frameworks, including collaborative, network, and cooperative models, this keynote delved into organizational, collaborative, and social innovation dynamics. It underscored the limitations of the status quo, where incremental change and reform fall short of achieving significant impact. Through a discourse about systemic innovation, the keynote discussed ways to produce desired outcomes that achieve measurable impacts with positive social change. TDC acts as a force multiplier for disruptive innovation initiatives, enabling a departure from conventional solutions and embracing holistic, system-wide transformations. The article concluded by highlighting the necessity of fostering a culture where TDC catalyzes disruptive innovation and offers a roadmap for tackling global challenges through unprecedented collaboration and creativity.